DETERMINAN PENDAPATAN ANGGOTA BANK SAMPAH MANDIRI (BSM) DI DESA PUNGGUL, KECAMATAN ABIANSEMAL, KABUPATEN BADUNG - Sekardadi, Ni Made Ayu; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 7 (2020): VOL 11 NO 7, JULI 2022 [2481-2899], 2022)
The population that grows is increasing every year which causes economic growth of both the population and the population to also increase, so that the volume of waste caused also increases. Punggul Village as a pilot village deserves to be an example in waste management through a waste bank. This study aims to see the effect of education level, number of family members and participation of members of the Mandiri Waste Bank (BSM) in Punggul Village, Abiansemal District, Badung Regency.This research uses primary data. Collecting data through interviews, questionnaires and observations. The data analysis technique used multiple linear regression analysis techniques. According to the analysis found that 1) Education level, number of family members and participation simultaneously have a positive and significant effect on BSM members in Punggul Village, Abiansemal District, Badung Regency, 2) Education level, number of family members and participation partially have a positive and significant effect on members of BSM Punggul Village, Abiansemal District, Badung Regency.     Keywords: Waste Bank, Education Level, Number of Family Members, Participation. Income